2017
DOI: 10.1186/s12941-017-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

Paramedical staffs knowledge and attitudes towards antimicrobial resistance in Dire Dawa, Ethiopia: a cross sectional study

Abstract: BackgroundThe continuing emergence, development and spread of pathogenic organisms that are resistant to antimicrobials are a cause of increasing concern. The control of antimicrobial resistance requires knowledge of factors causing antimicrobial resistance, good attitudes towards the intervention strategies as well as changes in antibiotic prescribing behavior of health workers. Hence, this study was aimed to assess paramedical staffs’ knowledge and attitudes towards antimicrobial resistance and their antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
4
27
1
Order By: Relevance
“…This finding is consistent with other studies which reported that patient's demands, as well as non-compliance to treatments and guidelines, contribute to AMR ( Moore and McNulty, 2012 ; Wang et al, 2019 ). This contrasted though with another study in Ethiopia which showed that more than three-quarters of nurses surveyed thought adherence or correct treatment were not important contributors to AMR ( Tafa et al, 2017 ); however, the authors suggested that topics of AMR should be embedded in their training curriculum.…”
Section: Discussionmentioning
confidence: 61%
“…This finding is consistent with other studies which reported that patient's demands, as well as non-compliance to treatments and guidelines, contribute to AMR ( Moore and McNulty, 2012 ; Wang et al, 2019 ). This contrasted though with another study in Ethiopia which showed that more than three-quarters of nurses surveyed thought adherence or correct treatment were not important contributors to AMR ( Tafa et al, 2017 ); however, the authors suggested that topics of AMR should be embedded in their training curriculum.…”
Section: Discussionmentioning
confidence: 61%
“…This could be true in settings where infection control knowledge, attitudes and practices among healthcare workers is poor in Ethiopia [60]. High frequency of inappropriate use of antibiotics and empirical therapies by healthcare professionals was also reported in Eastern Ethiopia [61]. In addition, the antimicrobial susceptibility testing method was based chiefly on disc diffusion and resistance was defined following the CLSI guideline.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies which reported that patient's demands, as well as non-compliance to treatments and guidelines, contribute to AMR (Moore and McNulty, 2012;Wang et al, 2019). This contrasted though with another study in Ethiopia which showed that more than three-quarters of nurses surveyed thought adherence or correct treatment were not important contributors to AMR (Tafa et al, 2017); however, the authors suggested that topics of AMR should be embedded in their training curriculum. In our study, less than one-third of the participants responded that reduced access to local antibiograms could lead to AMR.…”
Section: Discussionsupporting
confidence: 87%